Pathogenicity and copper tolerance in Australian Xanthomonas species associated with bacterial leaf spot. (January 2020) - Roach, R.; Mann, R.; Gambley, C.G.; Shivas, R.G.; Chapman, T.; Rodoni, B.
Abstract: Recent studies into the distribution of Xanthomonas species causing Bacterial Leaf Spot (BLS) in Australian solanaceous crops detail varied genomic profiles that may influence pathogenicity. These genomic studies are expanded upon here by reporting the pathogenicity, race and copper tolerance of the previously sequenced Xanthomonas strains. Capsicum (Yolo Wonder), tomato (Grosse Lisse) and differential lines of capsicum (Early Cal-Wonder) were used to determine pathogenicity and race. Copper tolerance of 44 Xanthomonas strains was measured by observing bacterial growth on copper sulphate amended media. Protein sequence associated with these traits was detected using genomic analysis and compared using protein alignments. Only strains of X. euvesicatoria (16 strains) were found to be pathogenic on both tomato and capsicum. These were determined to be race 4 and 9. High copper tolerance was detected in the majority of Xanthomonas strains tested. Multiple copper resistance and avirulence proteins were detected in genomic sequence. Relatively few of these were associated with plasmid sequences. The genomic basis for copper tolerance was determined to be complex, as the tolerance thresholds did not directly correlate with gene number or presence. Similarly, pathogenicity of the strains was also not always clearly linked with presence or absence of specific Avr genes. This study highlights the need for detailed and ongoing investigations into the function of these proteins and how they produce the phenotypes that affect crop production. Highlights: Australian X. euvesicatoria strains are pathogenic on both pepper and tomato and are races 4 and 9. Race genetics are complex and require further investigation. Australian BLS-associated Xanthomonas strains display a generally high level of copper tolerance. This copper tolerance does not directly correlate with copper resistance gene presence or plasmid presence.